2021
DOI: 10.3389/fpsyg.2021.712703
|View full text |Cite
|
Sign up to set email alerts
|

The Status and Influencing Factors of Cyberchondria During the COVID-19 Epidemic. A Cross-Sectional Study in Nanyang City of China

Abstract: Cyberchondria is considered “the anxiety-amplifying effects of online health-related searches.” During the COVID-19 pandemic, people are likely to search health-related information online for reassurance because of fear and related physical symptoms, while cyberchondria may be triggered due to the escalation of health anxiety, different online seeking behavior preference, information overload, and insufficient e-health literacy. This study aimed to investigate the status and influencing factors of cyberchondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 71 publications
3
14
0
Order By: Relevance
“…“WJX” is widely used in questionnaire research in China. It is efficient and reliable ( Peng et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…“WJX” is widely used in questionnaire research in China. It is efficient and reliable ( Peng et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…[ 29 ] However, the current study reported that there is a statistically significant association between high eHealth literacy and cyberchondria, which is in agreement with the findings of previous studies. [ 15 , 30 ] This may be explained by the fact that eHealth literacy is directly proportional to the time spent on, and the frequency of searching, the internet. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…A higher score indicates a higher severity of suspected cyberchondria. The psychometric properties of the Chinese version of the CSS-12 were reported by Peng et al [ 22 ].…”
Section: Methodsmentioning
confidence: 99%